The Dynamics of a Behavioral Two-Sex Demographic Model - Rune Johansen; John K. Dagsvik (Statistics Norway, Research Department, 1999)
In this paper, we examine the dynamic properties of a particular demographic model. An essential part of the model is the marriage function which is derived from assumptions about the behavior of women and men in a market where each individual is looking for a suitable partner. By means of simulation experiments we investigate different aspects of the model. Specifically, we find that it is difficult to determine parameters related to preferences, birth and death rates, such that a non-trivial stable equilibrium is attained.
Keywords: C78; J11; 330; Two-sex demographic models; Marriage function; Birth rates; Non-trivial equilibria